Menumbuhkan Generasi Literat Melalui Strategi Peningkatan Kegemaran Membaca pada Siswa Sekolah Dasar - Anita Puspa Meilina; Meysila Sesilia Putri; Bunga Regina Andini; Erliza Azzahra (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2026)
This study aims to analyze strategies for increasing reading interest in developing a literate generation among elementary school students and to identify factors influencing literacy culture within school and family environments. The phenomenon of low reading interest among elementary school students has become a significant concern because the rapid development of digital technology tends to shift students’ attention from reading activities to audiovisual entertainment. This research employed a descriptive qualitative approach using a case study method at SDN 1 Notoharjo. Data were collected through semi-structured interviews, observations, and documentation studies. The participants consisted of one classroom teacher and four third-grade students of SDN 1 Notoharjo. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was tested using source triangulation and method triangulation. The findings revealed that literacy strengthening was implemented through morning reading activities, book discussions, the use of visual and digital media such as e-books, and the utilization of reading corners and school libraries. The study also found that students’ reading interest was influenced by the availability of reading materials, the comfort of literacy environments, family support, and the dominant use of gadgets for entertainment purposes. This study contributes scientifically by strengthening the concept of collaborative literacy involving schools, families, and digital technology in developing reading culture among elementary school students. The findings imply the need for more integrated, adaptive, and sustainable literacy programs to improve students’ reading interest in the digital era.